2022
DOI: 10.1136/bmjdrc-2022-002801
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin protects neural and vascular dysfunction of the retina in diabetes

Abstract: IntroductionDapagliflozin, a sodium-glucose transporter inhibitor, effectively reduces blood glucose and is indicated for individuals with kidney diseases and cardiovascular disorders. In this study, we further expand the therapeutic benefit of dapagliflozin in the neural and vascular retina, with the potential to effectively manage diabetic retinopathy (DR), the most common complication of diabetes.Research design and methodsDb/db mice, an animal model of type 2 diabetes, were treated with dapagliflozin orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…However, the nerve fiber and ganglion cell layers were disorganized in these animals [33]. Furthermore, in diabetic db/db mice, DAPA effectively reduced the formation of acellular capillaries and improved the electroretinogram response [47]. Hu et al [35] demonstrated in STZ-induced diabetic mice that DAPA treatment improved the thickness of the inner nuclear and outer nu- clear layers of the neural retina by reducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the nerve fiber and ganglion cell layers were disorganized in these animals [33]. Furthermore, in diabetic db/db mice, DAPA effectively reduced the formation of acellular capillaries and improved the electroretinogram response [47]. Hu et al [35] demonstrated in STZ-induced diabetic mice that DAPA treatment improved the thickness of the inner nuclear and outer nu- clear layers of the neural retina by reducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by many studies using SGLT2 inhibitors [33,34,[45][46][47][48][49], the DR associated protective effects of DAPA in Akimba mice is potentially mediated by the improvement in long-term glycaemic control (8 weeks). However, recent studies have shown DAPA induced reductions in oxidative stress [46] and inflammation [46,47] improved retinal vascular and neural pathology in DR. Therefore, future studies should be carried out in the Akimba model to establish the role of oxidative stress and inflammation mitigated by SGLT2 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SGLT-2i appears to exert protective effects on vascular endothelial function, potentially benefiting retinal health by enhancing glycemic control, managing hypertension and hyperlipidemia, and protecting the blood–retinal barrier and retinal capillaries [ 76 ]. Indeed, rodent studies have shown the beneficial effects of SGLT-2i on ophthalmic complications of diabetes, and human studies indicated the ability to reduce diabetic macular edema [ 77 , 78 , 79 , 80 ]. However, in our study, we did not observe a lower risk of DR complications with SGLT-2i use.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic retinopathy is a common complication associated with diabetes, and the SGLT2i’s EMPA [ 45 ] and DAPA [ 46 ] have improved diabetic retinopathy in T2D db/db mice. Empagliflozin has also been shown to mitigate ocular edema and microaneurysms in the retina as well as inhibit the mammalian target of raptomycin activation.…”
Section: Use Of Selective Sglt2 Inhibition As An Antidiabetic Therapymentioning
confidence: 99%
“…Empagliflozin has also been shown to mitigate ocular edema and microaneurysms in the retina as well as inhibit the mammalian target of raptomycin activation. One of the characteristics of diabetic retinopathy in db/db mice is an increase in acellular capillary numbers [ 46 ], and DAPA has been shown to produce a substantial decrease in the acellular capillary numbers compared with placebo. Aside from this, inflammation is another main factor associated with diabetic retinopathy.…”
Section: Use Of Selective Sglt2 Inhibition As An Antidiabetic Therapymentioning
confidence: 99%